An approach to didactic-mathematical knowledge of future Basic Education teachers to teach elementary mathematics - Pincheira, Nataly (2021)
This paper presents a global analysis of the results obtained in an exploratory study about the didactic-mathematical knowledge (CDM) that future Basic Education teachers have in order to teach elementary mathematics. For this purpose, the math practices of 157 Chilean teachers under training were analyzed based on the CDM-Elementary Mathematics questionnaire, which includes six open ended questions to evaluate partial and initial aspects of such knowledge. The questions are based on the thematic areas proposed by the Chilean school curriculum and are closely related to the mathematical content of numbers and operations, patterns and algebra, measurement, geometry, data and probability. Results show that the level of performance obtained by future teachers is limited regarding didactic-mathematical knowledge for the different categories, when reaching an average of 24 points out of a total of 42. In addition, the thematic areas with the greatest difficulty are measurement, data, and probabilities. In conclusion, programs should be created to support teacher training in order to successfully address the teaching of elementary mathematics in the basic education classroom.